MIGRAN DAN MIGRASI: BEBERAPA PEMAHAMAN DALAM PERSPEKTIF BIBLIS - Yosef Masan Toron (Jurnal Alternatif Wacana Ilmiah Interkultural, 2014)
One in every fifty human beings has crossed borders as migrants.All indications are that the numbers of migrants and other uprooted peoples will continue to increase.Most migration today takes plece as a result of compelling circumstances.As is now widely recognized,the rising hostility towards mnigrants workers and other foreigners in so many societies,obviously exacerbated by the traumas ofrecession and unemployments, appears to be an ominous and malignat cancer spreading accorss aour societies.Therefore, authentic Christian faith must be lived in a world in which millions people have no home and are making demands on the countries to which they immigrate or are deported. What is the Church's attitude towards these people? How should people of the Church respond to the urgent needs of these human beings? Fr.Joe Masan Toron is empowering us to have the biblical perspectives to cope with migration and migrants workers in our society.